A fatal mongoose bite. (19th November 2012) - Tumram, Nilesh Keshav; Bardale, Rajesh Vaijnathrao; Dixit, Pradeep Gangadhar; Deshmukh, Ashutosh Yashwant
Abstract : Animal bite is a bite wound from a pet, farm or wild animal. Dog bites make up 80–85% of all reported incidents. Cats amount for about 10% of reported bites and other animals such as rodents, rabbits, horses, raccoons, bats and monkeys amount to 5–10%. Bites by mongoose are uncommon. Here, we present a case of fatal mongoose bite to an elderly woman who died as a complication of streptococcal infection at the bite site.